Interchain vs. intrachain energy transfer in acceptor-capped conjugated polymers. - Beljonne, D; Pourtois, G; Silva, C; Hennebicq, E; Herz, L; Friend, R; Scholes, G; Setayesh, S; Mullen, K; Bredas, J (2002)
The energy-transfer processes taking place in conjugated polymers are investigated by means of ultrafast spectroscopy and correlated quantum-chemical calculations applied to polyindenofluorenes end-capped with a perylene derivative. Comparison between the time-integrated luminescence and transient absorption spectra measured in solution and in films allows disentangling of the contributions arising from intrachain and from interchain energy-migration phenomena. Intrachain processes dominate in solution where photoexcitation of the polyindenofluorene units induces a rather slow energy transfer to the perylene end moieties. In films, close contacts between chains favors interchain transport of the excited singlet species (from the conjugated bridge of one chain to the perylene unit of a neighboring one); this process is characterized by a 1-order-of-magnitude increase in transfer rate with respect to solution. This description is supported fully by the results of quantum-chemical calculations that go beyond the usual point-dipole model approximation and account for geometric relaxation phenomena in the excited state before energy migration. The calculations indicate a two-step mechanism for intrachain energy transfer with hopping along the conjugated chains as the rate-limiting step; the higher efficiency of the interchain transfer process is mainly due to larger electronic coupling matrix elements between closely lying chains.